1099 ERGOREFLEX SENSITIVITY IS ASSOCIATED WITH CARDIAC INVOLVEMENT IN BECKER MUSCULAR DYSTROPHY. (15th December 2022) - Castiglione, Vincenzo; Sciarrone, Paolo; Torri, Francesca; Borrelli, Chiara; Barison, Andrea; Todiere, Giancarlo; Grigoratos, Chrysanthos; Siciliano, Gabriele; Passino, Claudio; Emdin, Michele; Ricci, Giulia; Giannoni, Alberto
Abstract: Background and aims: Becker muscular dystrophy (BMD) is a X-linked recessive inherited skeletal myopathy due to dystrophin deficiency ensuing in a variable phenotype characterized by slowly progressing muscle weakness and, often, the development of dilated cardiomyopathy. The relationship between muscle and cardiac involvement in BMD is yet to be clarified. We aimed to assess the association between ergoreflex sensitivity, a marker of skeletal muscle work regulating ventilatory and autonomic responses to exercise, and cardio-muscular involvement in BMD. Methods: Fifteen male BMD patients (median age 37 years [25-42]) underwent a comprehensive evaluation including ECG, biohumoral assessment (high sensitivity troponin T/I [hs-TnT/I], natriuretic peptides, soluble suppression of tumorigenesis 2 [sST2], catecholamines, creatine phosphokinase [CPK], myoglobin), cardiac magnetic resonance (CMR), and ergoreflex determination. Muscular phenotype was distinguished into "classic" (proximal weakness affecting the shoulders and pelvis with waddling gait) or "mild". Cardiac involvement was defined based on the presence of late gadolinium enhancement (LGE) at CMR. Ergoreflex sensitivity was calculated as the percentage of the ventilatory response to a handgrip exercise maintained by circulatory occlusion through the inflation of a forearm tourniquet (clamp) during the third minute of recovery compared with the third minute of recovery without clamp: [(Rec∕Ex) clamp − (Rec∕Ex) no clamp]∗100, where Ex is the mean ventilation during the last 30 s of exercise, Rec the mean ventilation during the last 30 s of the third minute of recovery. Results: Ten patients (67%) had a "classic" muscular phenotype. Nine patients (60%) had LGE at CMR (median number of segments 9 [6-12]). The percentage of patients with cardiac involvement was not different between those with "classic" or mild muscular phenotype. Patients with cardiac involvement had higher ergoreflex sensitivity (24% [8-38] vs. 4% [0-24], p=0.036), hs-TnI (9.8 ng/L [5.9-14.5] vs. 2.1 ng/L [1.7-4.5], p=0.018), and hs-TnT (24 ng/L [20-35] vs. 11 ng/L [5-20], p=0.012), but did not show significant differences in terms of cardiac chamber size or systolic function compared to those without LGE. Ergoreflex sensitivity correlated with biomarkers of both cardiac (hs-TnI, rho=0.654, p=0.008; hs-TnT, rho=0.529, p=0.043; sST2, rho=0.654, p=0.009) and muscular damage (CPK, rho=0.645, p=0.009), as well as with the number of LGE segments (rho=0.583, p=0.022). No difference in ergoreflex sensitivity was detected in patients with "classic" versus mild muscular phenotype. Conclusions: In BMD, there is no relationship between cardiac involvement and the muscular phenotype. Nonetheless, cardiac involvement in BMD is characterized by enhanced ergoreflex sensitivity, which is associated with biomarkers of both cardiac and muscular damage.